Risk-factors for non-adherence to antiretroviral therapy Fatores preditivos de não-adesão à terapia antiretroviral - Márcia Cristina Fraga Silva; Ricardo Arraes de Alencar Ximenes; Demócrito Barros Miranda Filho; Luciano Wagner de Melo Santiago Arraes; Mecleine Mendes; Ana Caroline de Sobral Melo; Paola Rebeka de Melo Fernandes (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
Cross-sectional study analyzed as case-control to identify risk factors for non-adherence to antiretroviral therapy. We studied 412 out-clinics HIV infected subjects of three public hospitals of Recife, Pernambuco. The objective was to examine the association between non-adherence to the antiretroviral therapy and biological, social-behavior and demographics and economic factors, factors related to the disease and/or treatment, factors related to life habits and depression symptoms. Variables significantly associated with non-adherence to antiretroviral therapy were: time elapsed since HIV diagnosis (p = 0.002), daily dose (p = 0.046), use of alcohol (p = 0.030) and past drug use (p = 0.048), and borderline p-values were found for educational level (p = 0.093) and family monthly income (p = 0.08). In the multivariable analysis, the factors that remained in the final model were family monthly income, time period with HIV infection and use of alcohol. No association was observed between non-adherence to antiretroviral therapy and gender, age, sexual orientation, marital status, educational level and place of residence. Based on our results and the local situation we suggest: assessment of social needs; training of partners and/or families on supporting adherence, creation of "adherence groups" to motivate and to reassure patients on the benefits of treatment; counseling and/or psychotherapy for alcohol drinkers. Estudo transversal com análise tipo caso-controle, que avaliou 412 pacientes de hospitais públicos do Recife - PE, com o objetivo de identificar fatores preditivos de não adesão à terapia antiretroviral. Verificou-se associação entre não adesão à terapia antiretroviral e aspectos biológicos, sócio-comportamentais e demográficos, econômicos, relacionados à doença e ao tratamento, aos hábitos de vida e aos distúrbios do humor. Variáveis com associação estatisticamente significante com não adesão na análise univariada foram: tempo de diagnóstico (p = 0,002), maior número diário de comprimidos (p = 0,046), uso ...